Hermaphrodites and the understanding of sexual difference in the early seventeenth century - Fontes da Costa, Palmira (2021)
Abstract: In this paper, I compare the ways in which three seventeenth-century physi-cians, Rodrigo de Castro, Caspar Bauhin and Jean Riolan, dealt in their works with the anatomical and social problems posed by the hermaphroditic body. I show that early seventeenth-century medical discourses on hermaphrodites have recourse to a diverse synthesis of theories, sources and medical cases and that they are influenced by cultural anxieties over the disruptive power of sexual ambiguity. Resumo: Este artigo compara a visão de três médicos seiscentistas, Rodrigo de Castro, Caspar Bauhin e Jean Riolan, sobre os problemas anatómicos e sociais suscitados pelo corpo hermafrodita. Da análise apresentada, conclui-se que os discursos médicos sobre hermafroditas dos primórdios do século XVII são de natureza sincrética e influenciados por receios relacionados com o poder disruptivo da ambiguidade sexual na sociedade.